Cytotoxic effects of vitamins K1, K2, and K3 against human T lymphoblastoid leukemia cells through apoptosis induction and cell cycle arrest. (6th August 2020) - Xu, Wencheng; Wu, Hongguang; Chen, Shuhe; Wang, Xiaoqin; Tanaka, Sachiko; Sugiyama, Kentaro; Yamada, Haruki; Hirano, Toshihiko
Abstract: The present study was undertaken to evaluate cytotoxic effects of vitamin K1 (phylloquinone), vitamin K2 (menaquinones), and vitamin K3 (menadione) against human T lymphoblastoid leukemia cells, Jurkat T cells, MOLT‐4 cells, and P‐glycoprotein‐expressing multidrug‐resistant MOLT‐4/DNR cells. Vitamins K2 and K3, but not vitamin K1, reduced viabilities of Jurkat, MOLT‐4, and MOLT‐4/DNR cells. The influence potency of vitamin K3 was larger than that of vitamin K2 in all of the three cell lines. MOLT‐4/DNR cells seemed to be more sensitive toward the effects of vitamins K2 and K3. The cytotoxicity of vitamins K2 and K3 on these leukemia cells seems to be related to apoptosis induction and cell cycle arrest. Vitamin K2 and K3 treatment induced cleavage of PARP obviously. Moreover, vitamins K2 and K3 specifically down‐regulated the expressions of cyclin A2 in all of the three cell lines. However, the effects of vitamins K2 and K3 on the cell cycle profiling in Jurkat, MOLT‐4, and MOLT‐4/DNR cells varied with the cell type. Vitamins K2 and K3 also decreased the viability of mitogen‐activated human peripheral blood mononuclear cells. Our observations suggest that vitamins K2 and K3 have bilateral cytotoxic effects on activated human peripheral lymphocytes and the human leukemic T cells. Abstract : Vitamins K2 and K3, but not vitamin K1, reduced viabilities of Jurkat, MOLT‐4, and MOLT‐4/DNR cells. The cytotoxicity of vitamins K2 and K3 on these leukemia cells seems to be related to apoptosis induction and cell cycle arrest. Vitamin K2 and K3 treatment induced cleavage of PARP obviously. Moreover, vitamins K2 and K3 specifically down‐regulated the expressions of cyclin A2 in the three cell lines. Vitamins K2 and K3 also decreased the viability of mitogen‐activated human peripheral blood mononuclear cells.